Biography as History - Barman, Roderick (Journal of the Canadian Historical Association / Revue de la Société historique du Canada)

(untitled) (The Canadian Historical Association / La Société historique du Canada, 2010)
Biography has been for the last fifty years the stepchild of history. Drawing on the author’s personal experience as a biographer and a reader of biographies, the article considers the reasons why most historians avoid biography, examines the three unproductive forms of the genre or “no gos” to be avoided by would-be biographers, discusses the five caveats that should guide those writing biographies, and indicates the ways in which biography can be employed to advance our understanding of the past. Despite being a genre abounding in problems, biography is both viable and valuable, a useful but not a major weapon in the historian’s arsenal.